MSME Taxpayer Morality and Awareness in Fulfillment of Obligations in Pandemic Times - I Gusti Ayu Purnamawati; Gede Adi Yuniarta; Elly Herliyani (International Journal of Organizational Behavior and Policy, 2023)
The negative growth in tax revenues was caused by slowing economic activity and fiscal incentives, especially in the MSME sector affected by the pandemic. This research effort analyzes the aspects of morality and awareness of taxpayers towards tax obligations through the development of attribution theory. The quantitative approach through this research uses 250 respondents who own MSMEs. The analysis model uses multiple linear regression with random sampling to collect data. Primary data collection uses a questionnaire through the form of google form. The study results found that the morality and awareness of taxpayers affected the fulfillment of their obligations during the pandemic period. So that the government in determining the direction of policies related to compliance such as improving services in the field of socialization to taxpayers so that they understand more about taxation and have an effect on increasing the intention to carry out tax obligations and making policies according to the conditions and abilities of the community. Taxpayer compliance, in this case, is very necessary, which leads to how taxpayers are obedient to tax rules.